Pestivirus infection in sheep and goats in Northern Saudi Arabia (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: The current research aims to elucidate the recent situation regarding Pestivirus infection among different age groups, sexes, and breeds of goats and sheep in northern Saudi Arabia. Materials and Methods: 850 serum samples representing 594 sheep and 256 goats were collected at the slaughterhouse in Rafha city. Results: Using enzyme-linked Immune Assay, the overall detected seroprevalence in sheep and goats was 24.5%; it was 30.5% in goats and 21.9% in sheep. The detected seroprevalence was higher in goats than in sheep, in females than in males, and in adults than in young. According to the breeds, the highest prevalence (47%) was observed in the Naime breed. Pearson chi-square analysis revealed a significant correlation between infection and animal species (p < 0.008), sex (p < 0.003), and breed (p < 0.000). Conclusion: The prevalence of Pestivirus in sheep and goats appears to be increasing in the Northern region and throughout the country.J. Adv. Vet. Anim. Res., 12(4): 1414–1420, December 2025http://doi.org/10.5455/javar.2025.l1001